Local Development Plan: An Avenue for University-Local Government-Community Collaboration for Sustainable Community Development - Bhatta, Thakur Prasad (Journal of Education and Research, 2017)
Sustainable development has been one of the top priorities in the present world. Community development programmes are considered important in achieving sustainability. Universities or educational institutions often talk about, and collaborate with community for its development. However, there is less attention to an institutional mechanism to include local government in the collaboration of university and community for designing and implementing sustainable community development programmes.  This paper advances a model of tripartite collaboration between the university, local government and community in promoting sustainable community development through a local development plan.  Drawing upon the thematic reviews of selective literature in the field of sustainable development, community development, university- community collaboration, and policies and practices of local development plan in Nepal, this paper, from the perspective of social dimensions of sustainable development, argues that the local development plan can be an avenue for collaboration between the university, local government and community for sustainable community development.